2009
DOI: 10.4065/84.8.702
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum A Toxin/Dimethyl Sulfoxide Bladder Instillations for Women With Refractory Idiopathic Detrusor Overactivity: A Phase 1/2 Study

Abstract: We completed a phase 1/2 trial to evaluate the safety and potential efficacy of direct intravesical instillation of a botulinum type A toxin/dimethyl sulfoxide (DMSO) solution for treatment of idiopathic detrusor overactivity in women. Twenty-five women with medication-resistant, urodynamic-confirmed idiopathic detrusor overactivity were enrolled. A total of 9 patients were treated in phase 1 of the study. Three patients were given a 66% dosing of solution; 22 patients received the full 300 units of botulinum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…This could provide an explanation for the rapid onset of response seen in the present study compared with the latency of response observed in clinical studies where the toxin is injected transurothelially. Intravesical instillation has previously been suggested as an alternative method of delivery , but no study has adequately investigated whether intravesical administration in humans without injection is sufficient for the agent to cross the urothelial barrier. The data presented in the present study provide evidence that this may be possible, although further experiments are required to assess the efficacy and safety of this approach before application in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This could provide an explanation for the rapid onset of response seen in the present study compared with the latency of response observed in clinical studies where the toxin is injected transurothelially. Intravesical instillation has previously been suggested as an alternative method of delivery , but no study has adequately investigated whether intravesical administration in humans without injection is sufficient for the agent to cross the urothelial barrier. The data presented in the present study provide evidence that this may be possible, although further experiments are required to assess the efficacy and safety of this approach before application in humans.…”
Section: Discussionmentioning
confidence: 99%
“…There is a recent report of using of dimethyl sulphoxide (DMSO) for liquid BoNT bladder instillation [82]. DMSO does not maintain the natural state of the BoNT protein, and must be formulated immediately before instillation.…”
Section: Potential For Liquid Instillation Of Bontmentioning
confidence: 99%
“…Only a few open-label studies have addressed the use of BoNT-A instillation in patients with IC/PBS or neurogenic bladder [30,31]. The outcomes of these open-label studies, like those of the animal studies, suggest that the BoNT-A instillation affects bladder afferent mechanisms rather than motor nerves and improves LUTS without significantly affecting detrusor contractility.…”
Section: Discussionmentioning
confidence: 95%